Pengembangan UMKM bagi Pengusaha Pemula: Studi Kasus Pendampingan di Kota Padang - Dhaifullah, Mhd Arya; Yustisia, Henny; Yuliana, Yuliana (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Abstract. Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving local and national economic growth, especially in creating jobs and increasing community income. However, new entrepreneurs in the MSME sector often face various challenges such as limited capital, lack of managerial experience, limited market access, and low utilization of digital technology. This study aims to analyze MSME development strategies for new entrepreneurs through a mentoring approach in Padang City. The method used is a case study with a qualitative descriptive approach based on literature analysis, government program reports, and observations of MSME mentoring practices in the field. The results of the study show that effective development strategies include entrepreneurship training, facilitation of licensing and access to financing, business digitalization, and the formation of business communities as a forum for collaboration and knowledge sharing. Structured and sustainable mentoring programs have been proven to increase the capacity of new businesses, accelerate technology adaptation, and expand their market networks. This study recommends the need for synergy between the government, academics, and the private sector in designing contextual and targeted mentoring programs, as well as encouraging the integration of entrepreneurial competencies into the vocational education curriculum.